The typology of the distribution of Edge: the propensity for bipositionality - Ulfsbjorninn, Shanti; Lahrouchi, Mohamed (Papers in Historical Phonology, 2016)
We discuss the grammatical conditions that can be imposed between segmental content (features) and syllable structure (positions) and how a representational preference can influence diachronic development. The discussion centers on the co-distribution of two properties: occlusivity and bipositionality. The first is the phonological feature that induces occlusivity and reduces amplitude (that is: |ʔ|, which we will refer to as Edge(*)), the second is the autosegmental structural property of belonging to multiple positions (which we refer to as ‘C.C’). Edge(*) and bipositionality have a universal affinity but they are not reducible to each other. Instead, the inherent diachronic tendency to preserve Edge(*) in bipositional structures can become grammaticalised through licensing conditions that dictate the alignment of the two properties. This can be expressed bidirectionally, forming two major language types. Type A has the condition stated from the featural perspective (Edge(*) must be found in C.C). While, Type B comes from the other direction (C.C must contain Edge(*)). Crucially, the same structure is diachronically stable: (Edge(*)-C.C). What varies is the distribution of those properties elsewhere (given the direction of licensing condition). Type A excludes Edge(*) from {#__,V_V}, while Type B excludes C.Cs without Edge(*). Although there is variation on this point, there is a UG component, because there are no anti-Type A/B languages where Edge(*) repels bipositionality.